Development of Science Literacy-Based Children's Science Books Integrated Local Potential of Madura - Mardiyana, Isna Ida; Pritasari, Ade Cyntia (Widyagogik, 2023)
Children's story books have an important role in the world of education, especially at the elementary school level. However, the availability of story books that support learning is still very limited. Therefore it is important to develop children's story books that can be used as a companion to textbooks and to train literacy from an early age. This study aims to develop children's science story books based on integrated scientific literacy in Madura local potential that are feasible in terms of validity, effectiveness, and attractiveness. This development research uses procedures 4-D models ( four D models ). The results showed that the development of children's science story books in terms of the validity aspect obtained an average percentage of 89% in the valid category, the effectiveness aspect obtained a classical completeness percentage of 93% in the effective category, and the attractiveness aspect obtained an average percentage of 100% in the attractive category. Based on the research data it can be concluded that the development of scientific literacy-based children's science story books that are integrated with the local potential of Madura is deemed feasible to use.